Back-Translation in Academic Writing: Malay EFL Students’ Engagement with Cross-Language Plagiarism in Islamic Higher Education - Pratama, Melgis Dilkawaty (Indonesian Journal of Integrated English Language Teaching, 2025)
Plagiarism remains a persistent issue among English as a Foreign Language (EFL) students, particularly when they rely on translation strategies to navigate academic writing. This study explores Malay EFL students’ understanding and practices of back-translation—a process of translating texts from English to Malay and back to English—which often leads to cross-language plagiarism. Using a mixed-methods sequential explanatory design, data were collected from 30 students at an Islamic university in Indonesia through written tasks, questionnaires, and online interviews. Content analysis, descriptive statistics, and thematic analysis were employed to analyse the data. Findings reveal that most students are unaware that back-translation constitutes plagiarism and lack sufficient knowledge of proper paraphrasing and citation practices when working with multilingual sources. Students frequently depend on translation tools such as Google Translate and Quillbot, which increases the risk of unintentional plagiarism. The study concludes that limited awareness of academic writing conventions in multilingual contexts contributes to cross-language plagiarism, highlighting the need for targeted instruction on translation ethics and academic integrity in Islamic higher education.